Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Let the first term be x and the common difference be d...so..x-(a-b)^3=(a+b)^3-x...so 2x=(a+b)^3+(a-b)^3=>2x=2a^3=>x=a^3=second term(ans)
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts